Mechanisms of Artistic Imagery in the Poetry Collection Sacrifices of Farewell by Abdullah Bashrahil - Abu Dabeel, Sultan Saeed (Journal of Arabic Language Sciences and Literature, 2025)
Artistic imagery holds a prominent place among the elements of poetic experience and occupies a significant space in literary studies. It serves as the poet’s tool for expressing thoughts and emotions, embodying vision and sentiment, and acts as a criterion for evaluating poetic prowess and artistic talent. Given this importance, the present study—adopting a descriptive-analytical approach—aims to explore the mechanisms of artistic imagery in Sacrifices of Farewell by the poet Abdullah Bashrahil. This is achieved by identifying its sources, analyzing its components and formation process, highlighting its manifestations, and examining its active role in the text.Accordingly, the study is structured into an introduction and two main sections. The introduction provides an overview of the poet and the characteristics of his collection, Sacrifices of Farewell. The first section investigates his concept of artistic imagery and its sources within the collection. The second section examines the formations of artistic imagery through its elements, including simile, metaphor, metonymy, and synesthesia. The study concludes that Bashrahil was influenced by his reality and the broader reality of his Arab and Islamic nation. At times, his imagery expresses sorrow over the state of the nation, while at others, it conveys optimism and joy in envisioning the future. He also addresses the issues of his time and distills his experiences into images that demonstrate his creative ability to blend traditional and modern rhetorical elements. By merging simile, metaphor, metonymy, and synesthesia, he crafts these images in a way that showcases his talent in shaping and reimagining them innovatively, elevating them beyond conventional ideas into realms of originality and creativity.
Keywords: Artistic Imagery; Sacrifices of Farewell; Bashrahil; Mechanisms